Design, synthesis and liquid crystalline behavior of ethyl 4-((4-alkoxyphenyl)diazenyl)benzoates. (24th March 2018) - Mehmood, Hasnain; Ahmad, Zahoor; Akhtar, Tashfeen; Siddiqi, Humaira M.; Iqbal, Asma; Hameed, Shahid; Tahir, Muhammad N.
ABSTRACT: A series of ethyl 4-((4-alkoxyphenyl)diazenyl)benzoate is synthesized and the liquid crystalline behavior studied. Synthesized compounds are characterized by FTIR, 1 H-NMR, Mass and single crystal XRD. Differential scanning calorimetry was carried out to study the phase transitions and enthalpy changes. Polarizing optical microscopy revealed the mesogenic properties. These techniques revealed that three compounds (2a, 2b, 2f) exhibit liquid crystalline properties in the range of 80–104°C. POM exhibiting focal conical fan like texture which revealed the presence of smectic phases suggestive of their use in LCD and temperature sensing devices, besides 2c can be used as green emitter in OLEDs.